Evaluation of different enzymatic treatment procedures on sugar extraction from microalgal biomass, experimental and kinetic study. (1st April 2018) - Shokrkar, Hanieh; Ebrahimi, Sirous
Abstract: The enzymatic hydrolysis of algae has already been investigated for bioethanol production. However, the effect of varying the sequence of adding enzymes on the extraction of sugars from microalgal biomass has not been explored yet. In addition, there is no attempt describing the effect of algal cellulose on starch hydrolysis of algae using α-amylase. This contribution presents the results of the enzymatic hydrolysis kinetics of mixed microalgal biomass under different sequence of adding enzymes and operational conditions. In the proposed kinetic model, the factors including enzymes inactivation, product inhibition, and the inhibitory effect of cellulose on α-amylase were considered. The kinetic model performed well in predicting algal carbohydrates hydrolysis trends at experimental conditions. The obtained results revealed that the highest yields of reducing sugar (99%) and glucose (97%), were obtained by adding enzymes with the sequence of first cellulases, second α-amylase, and third amyloglucosidase. However, the hydrolysis rate of microalgal carbohydrates by simultaneous adding of enzymes was substantially higher. Finally, a fed batch strategy was applied to procure a concentrated reducing sugar medium from the hydrolysis of microalgal biomass, which could contribute to improve the cost-effectiveness of the bioethanol production from microalgae. Highlights: Kinetic model was successfully describing the enzymatic hydrolysis of microalgae. The effects of different enzyme adding sequence on hydrolysis rate were examined. The hydrolysis rate by simultaneous adding of enzymes was substantially higher. The algal cellulose decreased the initial rate of algal starch hydrolysis. The concentrated reducing sugar medium was obtained by fed-batch strategy.